Intra-familial physical violence among Mexican and Egyptian youth - Rivera-Rivera, Leonor; Allen, Betania; Thrasher, James F; Chavez, Ruben; Fernandez-Ortega, Cielo; Galal, Osman; Lazcano-Ponce, Eduardo C (Revista de Saúde Pública, 2005)
OBJECTIVE: To determine the prevalence of experiencing intra-familial violence among Mexican and Egyptian youth and to describe its associated risk factors. METHODS: Data from questionnaires applied to 12,862 Mexican and 5,662 Egyptian youth, aged 10 to 19, who attended public schools were analyzed. Biviarate and logistic regression analysis were used to determine the relationship between socio-demographics, the experience of intra-familial violence and violence perpetration. RESULTS: The prevalence of having experienced intra-familial violence was comparable across the Mexican and Egyptian populations (14% and 17%, respectively). In Mexico, young men were more likely to have experienced such violence (OR=2.36) than women, whereas in Egypt, young women were at slightly greater risk than young men (OR=1.25). Older age, male gender and urban residence were independent correlates of experiencing intra-familial violence among Mexican youth. For Egyptian adolescents, in contrast, younger age, female gender and having non-married parents were independent correlates of victimization. Intra-familial violence victims were also more likely than non-victims to perpetrate violence (Mexico: OR=13.13; Egypt: OR=6.58). CONCLUSIONS: Mexican and Egyptian youth experienced intra-familial violence at a relatively low prevalence when compared with youth of other countries. A strong association was found between experiencing intra-familial violence and perpetrating violence.